Promoting Mental Health Literacy of 13-16-Year-Old Students: A Systematic Review - Asplund, Aino; Kummel, Maika; Laaksonen, Camilla; Erjavec, Karmen; Sakellari, Evanthia; Santala, Elina; Korhonen, Joonas (MDPI, 2026)
Purpose: The global rise in mental health challenges among adolescents has led to the development of targeted interventions, including those designed to promote young people's understanding and awareness of mental health. This systematic review aims to identify and evaluate interventions implemented among secondary school students with the goal of enhancing mental health literacy, and to assess their effectiveness in achieving this outcome.
Methods: This review was partially aligned with the PRISMA 2020 guidelines. Studies were retrieved from four electronic databases-CINAHL Complete, PubMed, Academic Search Elite, and ERIC-and supplemented by a limited number of relevant studies identified outside the systematic search. The analysis focused on the content, delivery, design, evaluation methods, and outcomes of mental health literacy (MHL) interventions conducted in secondary schools internationally.
Results: A total of 16 articles met the inclusion criteria. The articles described a variety of different MHL interventions (n = 12). The findings indicate that school-based MHL interventions have a positive impact on students' knowledge and understanding of mental health, but stigma reduction demonstrated less consistent effects. Study population, country, intervention content, delivery, methods, outcome measures, sample sizes and participants' age range varied notably across the studies.
Conclusions: Based on the evidence synthesized in this review, school-based MHL interventions appear to be effective and may serve as a valuable component in broader efforts to promote mental health in adolescence. These findings reinforce existing evidence and provide a foundation for practical implications, but future research is highly recommended for a more solid base of evidence.